PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM STRATEGI PEMASARAN JASA UNTUK MENINGKATKAN KEPUASAN PELANGGAN - Sinarwaty; Adithia Fitra Wulandari; Yuput Sustira (SINERGI : Jurnal Riset Ilmiah, 2026)
The rapid development of digital technology, particularly Artificial Intelligence (AI), has significantly transformed service marketing strategies. Service companies are required to deliver fast, accurate, and personalized services to meet increasing customer expectations. This study aims to analyze the utilization of AI in service marketing strategies and its impact on customer satisfaction. The research employs a quantitative approach, with data collected through questionnaires distributed to users of digital-based services. The data are analyzed using descriptive and inferential statistical methods. The results indicate that the use of AI technologies, such as chatbots, recommendation systems, and customer data analytics, has a positive and significant effect on customer satisfaction. This is because AI enhances service speed, information accuracy, and the personalization of customer experiences. Therefore, the implementation of AI in service marketing strategies can be an effective solution to improve service quality and organizational competitiveness. This study is expected to contribute to the development of technology-based service marketing strategies in the digital era.